Mammalian MAPK signal transduction pathways activated by stress and inflammation: a 10-year update - Kyriakis, John M; Avruch, Joseph (Physiological reviews, 2012)
The mammalian stress-activated families of mitogen-activated protein kinases (MAPKs) were first elucidated in 1994, and by 2001, substantial progress had been made in identifying the architecture of the pathways upstream of these kinases as well as in cataloguing candidate substrates. This information remains largely sound. Nevertheless, an informed understanding of the physiological and pathophysiological roles of these kinases remained to be accomplished. In the past decade, there has been an explosion of new work using RNAi in cells, as well as transgenic, knockout and conditional knockout technology in mice that has provided valuable insight into the functions of stress-activated MAPK pathways. These findings have important implications in our understanding of organ development, innate and acquired immunity, and diseases such as atherosclerosis, tumorigenesis, and type 2 diabetes. These new developments bring us within striking distance of the development and validation of novel treatment strategies. Herein we first summarize the molecular components of the mammalian stress-regulated MAPK pathways and their regulation as described thus far. We then review some of the in vivo functions of these pathways.